2017
DOI: 10.1080/10106049.2017.1408704
|View full text |Cite
|
Sign up to set email alerts
|

Step-wise Land-class Elimination Approach for extracting mixed-type built-up areas of Kolkata megacity

Abstract: The extraction of urban built-up areas is an important aspect of urban planning and understanding the complex drivers and biophysical mechanism of urban climate processes. However, built-up area extraction using Landsat data is a challenging task due to spatio-temporal dynamics and spatially intermixed nature of Land Use and Land Cover (LULC) in the cities of the developing countries, particularly in tropics. In the light of advantages and drawbacks of the Normalized Difference Built-up Index (NDBI) and Built-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It is worth noting that this represents an important improvement from estimates in McGranahan et al (2007a) and that newer, more recent estimates of global populations in the LECZ (Kulp and Strauss, 2019, which showcases Coastal-DEM) do not stratify by any urban-rural classes. Other studies have highlighted population in case-study cities (Small et al, 2018b;Ahmed et al, 2018;Khan et al, 2019), but these are not global in extent; others have focused on types of cities (such as ports, De Sherbinin et al, 2007, or megacities, Nicholls, 1995 at risk.…”
Section: Constructing Classes Along An Urban-rural Continuummentioning
confidence: 99%
“…It is worth noting that this represents an important improvement from estimates in McGranahan et al (2007a) and that newer, more recent estimates of global populations in the LECZ (Kulp and Strauss, 2019, which showcases Coastal-DEM) do not stratify by any urban-rural classes. Other studies have highlighted population in case-study cities (Small et al, 2018b;Ahmed et al, 2018;Khan et al, 2019), but these are not global in extent; others have focused on types of cities (such as ports, De Sherbinin et al, 2007, or megacities, Nicholls, 1995 at risk.…”
Section: Constructing Classes Along An Urban-rural Continuummentioning
confidence: 99%
“…The Normalized Difference Built-up Index (NDBI) proposed by Zha et al (2003) was developed by analyzing the spectral response of built-up elements in different bands of the Landsat TM image. Due to its simple mathematical computation and quick mapping, the index has been widely used for automatically mapping urban built-up areas from Landsat TM imagery (Zha et al, 2003;Mwakapuja et al, 2013;Khan et al, 2019;Hidayati et al, 2018). The Normalized Difference Water Index (NDWI) and the Modified Normalized Difference Water Index (MNDWI) formulated by McFeeters (1996) and Xu ( 2006) respectively, were based on the principle that built-up areas (impervious surfaces) are prone to have a lower moisture or water content than barren areas (pervious surfaces).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that among several tests, the merging of NDBI and MNDWI produced the highest accuracy of 90.3%. Khan et al (2019) compared the results of the NDBI index and the Built-up Area Extraction Method (BAEM) index through the mapping of built-up areas of Kolkata Megacity in India. The BAEM index, developed by Bhatti and Tripathi (2014), is an amalgamation and integration of Land Surface Temperature (LST), NDVI, and MNDWI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…560 It is worth noting that this represents an important improvement from estimates inMcGranahan et al, 2007b, and that newer, more recent estimates of global populations in the LECZ (Kulp and Strauss, 2019 which showcases CoastalDEM), do not stratify by any urban-rural classes. Other studies have highlighted population in case-study cities(Small et al, 2018b;Ahmed et al, 2018;Khan et al, 2019) but these are not global in extent; others have focused on types of cities (such as ports, De Sherbinin et al, 2007 or megacities,…”
mentioning
confidence: 99%